Analisis Rasio Keuangan dalam Pengukuran Kinerja Keuangan pada Perusahaan Sub-Sektor Rokok - Ananta, Mufita Dea; Adam Nurdin Naufaldy; Ratnasari, Bagas Firmansyah; Mochammad Fajar Saputra; Ratnasari, Cholis Hidayati (CV. Lenggogeni Data Publishing, 2024)
Research Aims: The cigarette industry is one of the leading segments of various sectors in Indonesia and is one of the largest commodities contributing to Indonesian state revenues obtained from Value Added Tax (PPN), Excise, and local taxes. The purpose of this study was to determine the performance of financial performance as measured by the value of financial ratios, namely profitability ratios, liquidity ratios, activity ratios, and solvency ratios of several companies engaged in the tobacco industry as a sample study. The results of this study revealed that there are some companies that have an increase in the value of financial ratios from year to year, but there are also companies whose value decreases in the following year, this indicates that financial ratios can describe financial performance over time and become a management benchmark in performance evaluation to improve company performance in the future.